2006
DOI: 10.1016/j.cub.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis

Abstract: What is in store for the guppy? Variation is essential to understanding the genetics underlying biological processes. The guppy provides a huge amount of natural variation that can be studied genetically. This variation has not been produced by mutagenesis screens, but instead has been shaped by natural selection. Thus, combined with emerging genomic resources, the guppy is an ideal organism for understanding the evolutionary genetics and molecular basis of adaptation.Where can I find out more?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
300
0
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(337 citation statements)
references
References 13 publications
2
300
0
35
Order By: Relevance
“…Furthermore, phylogenetic studies of a number of rhizoxinpositive isolates from all the five continents, delivered evidence for host switching of symbionts between fungal lineages (Lackner et al, 2009a), indicating that horizontal transmission has taken place during evolution of the symbiosis, and might still have a role in the natural environment. Yet, in each reproduction cycle of the fungus, B. rhizoxinica is passed on vertically to the next generation, which is a hallmark of close mutualistic relationships (Moran, 2006;Bright and Bulgheresi, 2010). Quite unexpectedly, we observed that the host is not capable of vegetative reproduction in the absence of endosymbionts.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Furthermore, phylogenetic studies of a number of rhizoxinpositive isolates from all the five continents, delivered evidence for host switching of symbionts between fungal lineages (Lackner et al, 2009a), indicating that horizontal transmission has taken place during evolution of the symbiosis, and might still have a role in the natural environment. Yet, in each reproduction cycle of the fungus, B. rhizoxinica is passed on vertically to the next generation, which is a hallmark of close mutualistic relationships (Moran, 2006;Bright and Bulgheresi, 2010). Quite unexpectedly, we observed that the host is not capable of vegetative reproduction in the absence of endosymbionts.…”
Section: Introductionmentioning
confidence: 66%
“…Many bacterial strains live in close associations with eukaryotic hosts, ranging from invasive parasites to obligate mutualists having vital roles for their hosts (Moran, 2006). In mutualistic associations, specialized mechanisms have evolved that guarantee the persistence of the symbiosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are either ectosymbiont or endosymbiont [1,2]. The evidences over the years prove that endosymbionts have important role in their hosts for immunity, nutrition and in defense [1].…”
Section: Introductionmentioning
confidence: 99%
“…Other symbionts are facultative, often infecting only a portion of a population, and without which hosts can survive and potentially thrive (O'Neill et al, 1997). Because such facultative symbionts usually cannot be cultivated outside their hosts, their roles remained obscure for many years (Moran, 2006). With the advent of molecular techniques, however, interest in these bacteria has escalated and it has become increasingly evident that facultative symbionts can have major effects on their host's biology, ecological relationships and evolutionary dynamics (Moran, 2006).…”
Section: Introductionmentioning
confidence: 99%